Analisis Ketimpangan Pembangunan dan Klasifikasi Wilayah antar kabupaten/kota Provinsi DKI Jakarta Tahun 2016-2020 - Thalaha, Aperire; Amara, Intan Fetriana; Desmawan, Deris (Universitas Labuhanbatu, 2022)
In DKI Jakarta Province, it was identified that economic growth in 2016 to 2020 was very different, therefore this proves that there is an imbalance between cities. Namely inequality in the province of DKI Jakarta. It is suspected that this is caused by the inequality between abundance, for example natural resources and human resources. This study aims to see the magnitude of the differences in development between cities in DKI Jakarta Province. Furthermore, research or analysis aims to pay attention to area grouping by measuring per capita income and economic growth. Williamson index analysis is to use the method in this study in order to have the aim of knowing how high the level of development gap is, and there is also a Klassen Typology analysis which is used to determine the area of the region. The average obtained after analyzing the Williamson Index from 2016 to 2020 is 0.5541.